Discrete absorption components in the massive LBV Binary MWC 314. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Lobel, A.; Martayan, C.; Corcoran, M.; Groh, J. H.; Frémat, Y.
Abstract: We investigate the physical properties of large-scale wind structures around massive hot stars with radiatively-driven winds. We observe Discrete Absorption Components (DACs) in optical Hei P Cygni lines of the LBV binary MWC 314 ( P orb = 60.8 d). The DACs are observed during orbital phases when the primary is in front of the secondary star. They appear at wind velocities between −100 km s −1 and −600 km s −1 in the P Cyg profiles of Hei λ5875, λ6678, and λ4471, signaling high-temperature expanding wind regions of enhanced density and variable outflow velocity. The DACs can result from wave propagation linked to the orbital motion near the low-velocity wind base. The Hei lines indicate DAC formation close to the primary's surface in high-temperature wind regions in front of its orbit, or in dynamical wind regions confined between the binary stars. We observed the DACs with Mercator-HERMES on 5 Sep 2009, 5 May 2012, and 6 May 2014 when the primary is in front of the secondary star. XMM-Newton observations of 6 May 2014 significantly detected MWC 314 in X-rays at an average rate of ~0.015 cts s −1 .